The formation of professional and ethical competencies among future specialists in the field of physical culture and sports - Dranyuk O.I.; Kraft N.N.; Baeva T.E. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to validate empirically the educational requirements for the development of professional and moral competencies in students at the University of Physical Education. Methods and structure of the study. The approach of theoretical examination and synthesis of scholarly publications, pedagogical insights, student surveys, expert evaluation, pedagogical experimentation, and statistical analysis (Mann-Whitney U-test) was employed. The verification of the study’s working hypothesis was conducted through experimental work as part of the students’ coursework in the subject «Professional Ethics». Results and conclusions. The findings of the research, which involved 234 first-year students at the University of Physical Culture, suggest that the majority of participants recognize the significance of ethical principles in human life and work. However, approximately half of the respondents would not rely on these principles when faced with moral dilemmas. The study has identified and experimentally validated the pedagogical factors that contribute to the development of professional and ethical competence among future professionals in the field of physical culture and sports.